Education and museums: The exercice of glance - Sibaja Hidalgo, María Antonieta (2018)
Education in museums exceedes the didactic  purpose and is related to art language and history of art. It is also important to draw the borderland with other artistic expressions based on image like movie picture and documentary. This is the aim of the article.